The Relationship Between Attention, Memory and Pupillometry - Nadas, Regina; Molnar, Gyorgy (IEEE International Conference and Workshop in Óbuda on Electrical and Power Engineering (Online), 2024)
The LC-NE (locus coeruleus norepinephrine) system works in parallel with cognitive capacity., thus determining and influencing performance and efficiency. The relationship between attention and memory is close and interdependent. The relationship between attention., memory and pupillometry has been the subject of a large body of research., the central theme of which is that pupil dilation is a reliable measure of cognitive effort., attention and memory processes. Pupillometry shows that pupil size increases when a person's attention is engaged in an increased cognitive load or memory task. This phenomenon is observed during both working memory and episodic memory recall. For example., pupil dilation may be associated with memory encoding and retrieval., as well as with the allocation of attentional resources Attention helps to select and process information., while memory stores this information for longer periods of time. The attentional focus of individuals influences which information is retained in memory over the long term. Pupillometry., which measures changes in pupil size., is a useful tool for investigating this relationship. Pupil size has been linked to cognitive load and attention intensity., so pupillometry offers a way to better understand attentional and memory processes. Consequently., in the present experiment we were to investigate how the efficiency of delayed recall of auditory stimuli is related to the level of attention., mind-wandering., and change in pupil size.